An Improved Breadth-First Search Method Based on Information Interaction Applied for Power Network Topology Analysis. (15th February 2023) - Bian, Haihong; Guo, Zhengyang; Wang, Ximeng; Zhou, Chengang; Bing, Shengwei; Zhang, Zhiyuan
Abstract : With the rapid development of new energy resources and diversified load, power network topology data have grown swiftly. To meet the needs of the smart grid dispatching system, the power network topology analysis to support the marketing, power distribution, and other businesses in the operation of the grid has become one of the bottlenecks in the development of the smart grid. In the power grid, the outgoing lines of some generators are directly connected to the transformer, and during the busbar analysis, the nodes only adjacent to the transformer components will be identified as independent busbars. Therefore, a new method of node numbering optimization is proposed, in which the nodes adjacent to the switch are numbered preferentially. On this basis, a new abstract description method of adjacency relations and an improved breadth-first search method based on information interaction are proposed. Finally, simulation experiments are carried out in power grids with three different scales. The simulation results show that the algorithm can quickly and accurately realize power network topology analysis in the large-scale power grid, and the operating efficiency is improved by about 20% compared with the traditional algorithm.